PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO DAN TOTAL ASSETS TURN OVER TERHADAP RETURN ON ASSETS PADA PT. HANJAYA MANDALA SAMPOERNA TBK - Karolina, Karolina; Hidayat, Arif (Yayasan Education and Social Center, 2025)
The purpose of this study is to identify and analyze the influence of the Current Ratio (CR), Debt to Equity Ratio (DER), and Total Asset Turnover (TAT) on Return on Assets (ROA) at PT. Hanjaya Mandala Sampoerna Tbk, both partially and simultaneously. This research uses secondary data obtained from the company's annual financial statements for the period 2013 to 2023. This time frame was chosen to provide a comprehensive overview of the company’s long-term financial performance. The research sample consists of financial reports spanning those eleven years. Based on the results of multiple linear regression analysis, it was found that the Current Ratio does not have a significant effect on Return on Assets. This is indicated by the calculated t-value of 0.506083, which is less than the t-table value of 2.36462, and a significance value of 0.6283, which is greater than 0.05. Thus, the liquidity ratio does not affect the efficiency of asset management in generating profit for the company